Pengaruh Penggunaan Media Pembelajaran Power Point terhadap Motivasi Belajar Siswa di SMK Bina Islam Mandiri Kersana - Muqoronatur Rohmah; Faisal Rahman Dongoran (Jurnal Penelitian, Pendidikan dan Pengajaran: JPPP, 2021)
The purpose of this study was to determine the effect of power point learning media on student motivation at SMK Bina Islam Mandiri Kersana. The method of data collection in this study was to distribute questionnaires to 19 PPL students. The data analysis technique in this study used simple linear regression SPSS 20. From the results of the analysis of the coefficient of determination obtained a value of 21.5% which means that the use of powerpoint media has a contribution to student learning motivation of 21.5% while the t test value is obtained at 0.045 which means the use of power point learning media has an effect on students' learning motivation.